2016
DOI: 10.1016/j.aju.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser cystolithotripsy under local anaesthesia: Our experience

Abstract: ObjectiveTo investigate the feasibility and effectiveness of transurethral holmium laser cystolithotripsy (HLC) under local anaesthesia using a flexible cystoscope.Patients and methodsA prospective study was undertaken from January 2013 to June 2015. In all, 37 men with bladder calculi underwent HLC under local anaesthesia, preferably in a lithotomy position using a flexible cystoscope, followed by per urethral Foley catheter placement postoperatively.ResultsThe mean (SD; range) patient age was 46.6 (5.6; 32–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…On the other hand, they discovered no di culties throughout the follow-up period of six months. According to our short-term follow-up data, it was found that no stone recurrence was discovered in our study [59]. Based on our research and that of Agawal et al, we advise using a transurethral resectoscope with a high power laser setting for more effective fragmentation of urinary stones.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, they discovered no di culties throughout the follow-up period of six months. According to our short-term follow-up data, it was found that no stone recurrence was discovered in our study [59]. Based on our research and that of Agawal et al, we advise using a transurethral resectoscope with a high power laser setting for more effective fragmentation of urinary stones.…”
Section: Discussionsupporting
confidence: 61%
“…Again in the same study, authors concluded that open surgery presents higher complication rates than the endoscopic approach (19). Currently, it is well known that open surgery is the technique of choice for limited indications such as cases with oversized bladder stones or those, who are scheduled to undergo simultaneous prostatectomy or diverticulotomy (20). In obese patients, on the other hand, open surgical approach should be the last resort in our opinion.…”
Section: Resultsmentioning
confidence: 87%
“…The stones fragmented with the Ho:YAG laser can be retrieved by Ellik evacuator/ Toomy glass syringe wash or can pass spontaneously. 28,29 But the quality of dust and fragmentation attained with TFL is far minute compared to HO: YAG laser, thus obviating the need for the wash or extraction of the stone. This was our observation as all our patients with stones <20 mm passed the stone dust spontaneously and completely as was evident on the follow-up ultrasound which documented 100% stone clearance.…”
Section: Discussionmentioning
confidence: 99%